Pelatihan Pembuatan Boneka Tangan Limbah Blangkon Sebagai Media Sosialisasi Pemenuhan Hak dan Perlindungan Anak untuk Forum Anak Surakarta - Aquilla Miko Satria Nugraha; Miladi Muhammad; Suci Sepengasih (Universitas Hasanuddin, 2020)
Abstract Indonesia has ratified the Convention on the Rights of the Child based on Presidential Decree no. 36 of 1990 and has published Law No. 35 of 2014 on Amendment to Law no. 23 of 2012 on Child Protection, which is called one part by the community about 4 basic rights of children; Right to Life, Right to Grow, Right of Protection and Right of Participation. The Children's Forum is a children's communication organization that is used to form a project, has tasks that disseminate the rights. Seizing and fulfilling in reality socialization media is considered boring. Local cultural assets, including blangkon, can also be used in socialization media to fulfill the rights and protection of children. Blangkon waste is often simply dumped into the river and burned to the point of environmental pollution, and the shipping that can be used for the raw material of an interesting socialization media.